Estudio psicosocial sobre las representaciones sociales de género (2013)
The analysis of the representations was made through a Free Word Association method to a number of inducing stimuli. The results of a multidimensional scaling that associates the seven inducing stimuli clearly show two semantic fields: the first includes inequality and violence as inducing stimuli, and the second is formed by man, masculine, woman, feminine as stimuli. The formation of the semantic field indicated similarity, a relationship of proximity among the associated terms. The analysis and the discussion of the findings are constructed around the social representations of what is masculine and feminine.